PTU-268 The impact of EWTD on gastroenterology training and the inpatient GI referral service at a district general hospital. (28th May 2012) - Chhaya, V; Alexakis, C; Mendall, M; Gupta, S
Abstract : Introduction: A Specialist Registrar's (SpR) weekly duties include two Consultant and one SpR ward round, two clinics, 1–2 endoscopy training lists along with on-calls for General Medicine (GIM). Ward referrals are not included in the timetable. Since the implementation of the European Working Time Directive (EWTD), it has become increasingly difficult to get Gastroenterology (GI) training within the specified working hours. We aim to quantify the impact of EWTD on endoscopy training and the GI referral service at our hospital which serves 350 000 people. Methods: Data for GI referrals (excluding GI bleeds and endoscopy requests) was collected by two SpRs from November 2010 to September 2011. All ward referrals were seen within 24 h. An average duration of 20 min was used to see each referral which included a history, examination, review of medical records and documenting a proposed management plan. The average number of weekly referrals and standard rota details were used to analyse the impact of this activity for the year. Results: 515 referrals were seen over a period of 11 months with a mean age of 60 years (range 14–98). 22% were over 80 years and 54% were female. On average, 12 referrals were seen per week resulting in a total of 4 h and 57% were reviewed by a Consultant. Reasons for referral included liver disease (21%), inflammatory bowel disease (15%), hepatobiliary and pancreatic disease (13%), ERCP (13%), upper GI conditions (12%), lower GI conditions (9%), PEG (8%) and other miscellaneous conditions (9%). Conclusion: In a year of 260 working days, 35 days were spent on-call for GIM and 21 for night on-calls (1 in 5 rota). Due to EWTD restrictions, a further 28 days were lost on compensatory leave and 32 on annual leave leaving 144 working days. Only 2.8 days (number of working days remaining/260 working days x number of working days in the week) or 6 sessions per week are spent as a GI trainee. Clinics and ward rounds are fixed commitments leaving trainees to attend endoscopy lists within the remaining time. Due to shift patterns, SpRs are spending more time on the wards. Prospective cover for colleagues produces further challenges. This hinders endoscopy training and leaves referrals to be seen after working hours. We calculate that only 43% of training lists are attended in the year according to electronic records with endoscopy time recovered on non-training lists. Referrals add 4 h to the average week and although this is invaluable experience, the time is largely unaccounted for. This survey demonstrates the strains of modern rotas on endoscopy training and ability to see referrals. We suggest appropriate resourcing of the inpatient GI referral service with greater integration between GI and GIM rotas. Competing interests: None declared.